Copper-Induced Activation of Mapks, Cdpks and Camks Triggers Activation of Hexokinase and Inhibition of Pyruvate Kinase Leading to Increased Synthesis of Asc, Gsh and Nadph in Ulva Compressa - Moenne-Munoz, A; Laporte-Poblete, D; Gonzalez-Figueroa, A (Frontiers Media S.A., 2020)
In order to analyze whether copper induces activation of CaMK, CDPK and/or MAPK signaling pathways leading to carbon flux reprogramming and to the synthesis of ascorbate (ASC), glutathione (GSH) and NADPH in order to buffer copper-induced oxidative stress, U. compressa was initially cultivated with 10 µM copper for 0 to 10 days. The activities of hexokinase (HK), pyruvate kinase (PK), L-galactone 1,4 lactone dehydrogenase (L-GLDH) and glucose 6-P dehydrogenase (G6PDH) were analyzed. HK activity was increased whereas PK was inhibited, and L-GLDH and G6PDH activities were increased indicating a copper-induced modulation of glycolysis leading to carbon flux reprogramming. Then, the alga was cultivated with an inhibitor of CaMs and CaMKs, CDPKs and MAPKs, and with 10 µM of copper for 5 days and the activities of HK, PK, L-GLDH, G6PDH and glutathione synthase (GS), the levels of ASC/DHA, GSG/GSSG and NADPH/NADP, the levels of superoxide anions (SA) and hydrogen peroxide (HP) and the integrity of plasma membrane were determined. The activation of HK was dependent on MAPKs, the inhibition of PK on CDPKs/MAPKs, the activation of L-GLDH on MAPKs, the activation GS on CDPKs/MAPKs, and the activation of G6PDH on MAPKs. Increases in the level of ASC/DHA were dependent on activation of CaMKs/CDPKs/MAPKs, those of GSG/GSSG on MAPKs and those NADPH/NADP on CaMKs/CDPKs/MAPKs. The accumulation of superoxide anions and hydrogen peroxide and the integrity of plasma membrane were dependent on CaMKs/CDPKs/MAPKs. Thus, copper induced the activation of MAPKs, CDPKs and CaMKs leading to the modulation of glycolysis and carbon flux reprogramming which trigger an increase in ASC, GSH and NADPH syntheses and the activation of antioxidant enzymes in order to buffer copper-induced oxidative stress in U. compressa. © Copyright © 2020 Laporte, González and Moenne.